Homogeneous Li+ Flux Distribution Enables Highly Stable and Temperature‐Tolerant Lithium Anode - Fan, Chao‐Ying; Xie, Dan; Zhang, Xiao‐Hua; Diao, Wan‐Yue; Jiang, Ru; Wu, Xing‐Long (Advanced functional materials, 2021)
3D carbon hosts can enable low‐stress Li metal anodes (LMAs) with improved structural and interfacial stability. However, the uneven Li+ flux and large concentration polarization, resulting from intrinsically poor Li affinity and limited porosity of carbon scaffolds, make the precise control of Li plating/stripping still one the key challenges facing advanced LMAs. Here it is demonstrated that a lightweight carbon scaffold, featuring parallel‐aligned porous fibers, can work well for homogeneous Li+ flux distribution and reduced concentration gradient to form a stable solid electrolyte interphase, and then synergistically guide smooth Li nucleation/growth even at low temperatures. As a result, the obtained LMAs delivers a high areal capacity up to 15 mAh cm−2, ultralong lifespan (4800 cycles at 4 mA cm−2) with very low voltage hysteresis of ≈21 mV, a high practically available specific capacity of 863.9 mAh g−1 after 1000 cycles, and a long‐term stable behavior at low‐temperature operation. As coupling with the commercial LiNi1/3Co1/3Mn1/3O2 cathodes and common carbonate‐based electrolyte, the corresponding practical cells also possess an ultralong lifespan and outstanding low‐temperature functionality. This study not only presents an advanced carbon host candidate but also sheds new light on crucial design principles of carbon scaffolds for practically feasible rechargeable metal batteries. A lightweight carbon scaffold with a parallel‐aligned pattern achieves homogeneous Li+ flux distribution and reduces the concentration gradient to guide smooth Li nucleation/growth even at high‐power output and extreme temperatures. Accordingly, the prepared lithium metal anodes deliver a high areal capacity, ultralong lifespan with very low voltage hysteresis of ≈21 mV, and long‐term stable behavior at low‐temperature operation.